ISG20 stimulates anti-tumor immunity via a double-stranded RNA-induced interferon response in ovarian cancer - Chen, Zhigao; Yin, Min; Jia, Haixue; Chen, Qian; Zhang, Hongbing (Frontiers in Immunology, 2023)
Augmentation of endogenous double-stranded RNA (dsRNA) has become a promising strategy for activating anti-tumor immunity through induction of type I interferon (IFN) in the treatment of ovarian carcinoma. However, the underlying regulatory mechanisms of dsRNA in ovarian carcinoma remain elusive. From The Cancer Genome Atlas (TCGA), we downloaded RNA expression profiles and clinical data of patients with ovarian carcinoma. Using the consensus clustering method, patients can be classified by their expression level of core interferon-stimulated genes (ISGs): IFN signatures high and IFN signatures low. The IFN signatures high group had a good prognosis. Gene set enrichment analysis (GSEA) showed that differentially expressed genes (DEGs) were primarily associated with anti-foreign immune responses. Based on results from protein-protein interaction (PPI) networks and survival analysis, ISG20 was identified as a key gene involved in host anti-tumor immune response. Further, the results show that elevated ISG20 expression in ovarian cancer cells leads to increased IFN-β production. The elevated interferon improved the immunogenicity of tumor cells and generates chemokines that attract immune cells to infiltrate the area. Upon overexpression of ISG20, endogenous dsRNA accumulated in the cell, stimulating IFN-β production through the Retinoic acid-inducible gene I (RIG-I)-mediated dsRNA sense pathway. And the accumulation of dsRNA was proved to be associated with the ribonuclease activity of ISG20. By targeting ISG20, this study may facilitate the development of a potential immune therapeutic approach to treat ovarian cancer.